Gulag : a history - Applebaum, Anne, 1964- (Anchor Books, 2004)
A fully documented history of the Soviet camp system, from its origins in the Russian Revolution to its collapse in the era of glasnost. Anne Applebaum first lays out the chronological history of the camps and the logic behind their creation, enlargement, and maintenance. Applebaum also examines how life was lived within this shadow country: how prisoners worked, how they ate, where they lived, how they died, how they survived. She examines their guards and their jailers, the horrors of transportation in empty cattle cars, the strange nature of Soviet arrests and trials, the impact of World War II, the relations between different national and religious groups, and the escapes, as well as the extraordinary rebellions, that took place in the 1950s. She concludes by examining the disturbing question why the Gulag has remained relatively obscure, in the historical memory of both the former Soviet Union and the West.